The Impact of Global Trends on Tourism and the Creative Economy in Lampung Province - Mega, Selfia Alke; Barusman, M. Yusuf S; Habiburahman, Habiburahman; Barusman, Andala Rama Putra (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze the influence of global trends on the development of tourism and creative business sectors in Lampung Province. Methodology/approach: The research employs a qualitative approach through a systematic literature review, drawing data from scientific articles, research reports, books, and official statistical sources. Results/findings: Global trends such as the rise in tourist visits, digitalization, and environmental awareness significantly impact local economic growth, tourism product diversification, and promotional activities in Lampung Province. Conclusions: Global trends including the growth of tourist arrivals, diversification of tourism products, the emergence of digital tourism ambassadors, and increased environmental awareness have significantly influenced the tourism and creative business sectors in Lampung Province. These developments present both opportunities and challenges that require strategic adaptation and collaboration among local governments, business actors, and communities. By adopting digital technologies, promoting sustainable tourism practices, and leveraging cultural and natural resources, Lampung can strengthen its competitiveness and achieve sustainable regional development. Conclusion: This study shows that adaptation to global trends supports tourism and creative economy development in Lampung Province through digitalization, diversification, and sustainability. The findings underline the role of local innovation and stakeholder collaboration in regional development and suggest the need for stronger digital capacity and sustainable tourism policies Limitations: This study is limited to literature-based analysis and does not include empirical field data to validate the findings. Contribution: The research provides strategic recommendations for policymakers and business stakeholders to capitalize on global trends for developing sustainable tourism and creative industries in Lampung Province.